IMPLEMENTASI APLIKASI HAYATVERSE SEBAGAI SISTEM INFORMASI MANAJEMEN UNTUK MENINGKATKAN KUALITAS PELAYANAN ADMINISTRASI PENDIDIKAN - Ariatpi, Fina; Mulyawan Safwandy Nugraha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Digital transformation in education is an urgent need to improve the efficiency and quality of administrative services. This study aims to evaluate the implementation of the Hayatverse application as a management information system in improving the quality of education administration services. The research method used is qualitative with a direct observation approach and semi-structured interviews. Observations were conducted to understand how the application is used in the daily context, while interviews were conducted with parents and teachers as the main users of the application. The results show that the Hayatverse application is able to provide various benefits, including simplifying student data management, speeding up administrative processes, and increasing transparency and user involvement. Parents appreciate the app's features that make it easy to access their children's academic information, while teachers find it efficient in administrative and reporting tasks. However, challenges in implementing the app include the need for user training and upgrading the technology infrastructure in schools. In conclusion, the Hayatverse app has great potential to support digital transformation in education, especially in improving the quality of administrative services. Recommendations include developing features that are more responsive to user needs, improving data security, and a comprehensive training strategy.